PERJANJIAN KERJA ANTARA PIHAK PENYEDIA JASA KEAMANAN DENGAN PIHAK PENGGUNA PERBANKAN: ANALISIS YURIDIS, PERLINDUNGAN HUKUM, DAN IMPLIKASI KELEMBAGAAN - Arif Hidayat; Zuhrah Zuhrah; Nasrullah Nasrullah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study examines the legal construction of employment agreements between security service provider companies and commercial banks within the framework of Indonesian labor law and banking law. The complexity of this legal relationship stems from the fact that security personnel assigned to bank premises are administratively bound to the provider company, yet operationally supervised by and directly serving the interests of the bank, thereby generating a triangular employment pattern that risks blurring the boundaries of legal responsibility among the three parties involved. Employing normative legal research through statutory, conceptual, and case approaches, this study systematically analyzes the validity of outsourcing employment agreements, the mechanisms of legal protection afforded to security workers, the prudential principles mandated for banks under Financial Services Authority Regulation Number 9/POJK.03/2016, and the institutional implications arising from cross-sectoral supervision involving the Ministry of Manpower, the Financial Services Authority, and the Indonesian National Police as the technical supervisor of security service business entities. The findings indicate that although Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021 have clarified the responsibilities of outsourcing companies, these provisions have not fully accommodated the distinctive characteristics of the banking sector, which demands heightened security standards and layered supervision, leaving normative gaps that permit overlapping accountability and inadequate protection of security workers' rights. The novelty of this research lies in its simultaneous integration of labor law, banking law, and police regulatory law, a cross-regime approach seldom found in prior literature that has generally addressed outsourcing issues in a partial manner confined to labor law alone. The study concludes by recommending strengthened technical regulation through standardized tripartite cooperation agreement guidelines, harmonized cross-institutional supervision, and an explicit assertion of joint liability on the part of banks as the ultimate users of security services to close the persisting protection gap experienced by banking security personnel.